What do economists tell us about venture capital contracts? - Tereza Tykvová (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
Venture capital markets are characterized by multiple incentive problems and asymmetric information in an uncertain environment. All kinds of agency problems are present: moral hazard, adverse selection, hold-up problems, window dressing, etc. Entrepreneurs and venture capitalists enter into contracts that influence their behavior and mitigate the agency costs. In particular, they select an appropriate kind and structure of financing and specify the rights as well as the duties of both parties. The typical features of venture capital investments are: an intensive screening and evaluation process, an active involvement of venture capitalists in their portfolio companies, a staging of capital infusions, the use of special financing instruments such as convertible debt or convertible preferred stock, syndication among venture capitalists, or a short investment horizon.
Keywords: G32; G24; D8; 330; Venture Capital; Agency Costs; Risikokapital; Agency Theory; Unternehmensgründung; Leistungsanreiz; Vertrag; Anreizvertrag; Theorie